The Etiopathogenesis of Myofacial Pain Dysfunction Syndrome - Subhalaxmi Kar (Institute of Medico-legal Publications Pvt Ltd, 2020)
This article presents a review of revisiting the Etiopathogenesis of myofacial pain dysfunction syndrome.This article concentrates on the appropriate evaluation, causes and management of MPDS. Myofacial painis one of the significant and common reasons for the orofacial pain that originate from the myofacial triggerpoint. Patient with myofacial pain dysfunction syndrome also complains of a chronic musculoskeletal painon which pressure on a sensitive muscle or point cause pain.